Techno-economic analysis and life cycle assessment of a novel air-sourced high-temperature heat pump with hourly resolution - Moore, Dalton, author; Bandhauer, Todd, advisor; Quinn, Jason, committee member; Herber, Daniel, committee member (Colorado State University. Libraries, 2026)
As the decarbonization of the industrial sector becomes increasingly relevant in the energy transition, electrically-driven technologies offer the potential to decarbonize industrial heat currently produced by natural gas combustion. By upgrading heat, high-temperature heat pumps offer a competitive solution with higher emissions reduction potential as compared to electric resistance boilers. While current work on large-scale heat pumps typically focuses on waste heat sources, ambient air-sourced heat pumps offer higher flexibility and a wider range of applicability for customers. A techno-economic analysis and coupled life cycle assessment of a novel steam-generating air-sourced heat pump was conducted, with a comparison to a capacity-matched electric resistance boiler and natural gas boiler. The impacts of time-of-use utility rate structures with hourly cost resolution and typical localized weather patterns are investigated. In addition, the potential decarbonization pathways of each technology are explored to further quantify future steam solutions as the grid trends towards renewable generation technologies. The study found that the electric resistance boiler is a generally unattractive option compared to heat pumping from both a cost and emissions standpoint. It was determined that, at the studied locations, the natural gas boiler generally offered a cheaper solution economically in the non-renewable case for the current studied time and locations. For the renewable technologies, the heat pump was found to be typically cheaper. When considering emissions reduction and decarbonization cost, the heat pump provided the best value across most scenarios.
Keywords: heat pump; life cycle assessment; techno-economic analysis; industrial heat; decarbonization; steam